Desain 3 Dimension Baby Incubator Using SketchUp Application Based On Indonesia National Standars - Fatwasauri, Icha; Zaini, Anshari Ahmad (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2024)
Premature birth is one of the causes of perinatal death. Premature babies have a higher risk of death because babies find it difficult to adapt to life outside the womb due to immature organ systems of the baby's body. Medical devices used to maintain babies born prematurely are called incubators. In making incubators, usually before being made, you must try making a prototype first. In addition, it must also be simulated so that the results of the incubator are up to standard. Various studies related to simulators have been conducted, such as using matlab. This takes a relatively long time to learn. So the author designed the 3-dimensional design of the incubator is a cutting. Sketchup is easier to learn for beginners, this software is also free. The research method that researchers use is research and development. Researchers carry out several stages, namely literature study, initial design, 3-dimensional design, validation, and discussion. From the results of the design that has been made and given a questionnaire to material experts, a value of 67% or said to be feasible. Validation is also carried out by direct measurement and the results are not much different